Experimental Study on the Effect of Skin Flexibility on Aerodynamic Performance of Flapping Wings for Micro Air Vehicles - Hamid, Yusoff; M. Z., Abdullah; Kamarul Arifin, Ahmad; M. K., Abdullah; Shafiq, Suhaimi (scientific.net, 2014)
In the present study, the aerodynamic characteristics such as time-averaged lift and drag generation of two flexible membrane (latex thin and thick) wings with different skin flexibilities are compared with those of a conventional rigid (wood) wing to assess the effects of skin flexibility (rigidity) on the aerodynamic performance for flapping flight applications. The experiments are performed in an open circuit wind tunnel of non-return airflow with a test section of (0.3m x 0.3m) and is capable of speeds from 0.5 to 30 m/s. The time-averaged lift and drag as functions of flapping frequency, forward flight velocity and the orientation angle of the flapping motions with respect to the incoming flows are measured by using a strain gauge balance and KYOWA PCD-300A sensor interface data acquisition system. It has been found that flapping motion would bring significant aerodynamic benefits when the flapping flight is in unsteady state regime, with advance ratio less than 1.0. The aerodynamic benefits are found to decay exponentially with the increasing advance ratio. Flapping motion is found to become detrimental for high speed flight applications. It is also observed that the skin flexibility has considerable effect on the aerodynamic performance. The flexible latex thick wing is found to have better overall aerodynamic performance over the rigid wing, especially for low speed applications. The wood (rigid) wing exhibited better lift production performance in quasi steady regime.